Green Accounting Terhadap CSR pada Bus di Indonesia dengan Kinerja Keuangan Sebagai Variabel Intervening - Ulul Azmi Mustofa; Rezha Nia Ade Putri Edy; Muhammad Kurniawan; Muhammad Fikri Nugraha Kholid (Jurnal Ilmiah Ekonomi Islam, 2020)
Sustainability reporting is a financial reporting concept in banks that provides information covering economic, social and environmental aspects by taking into account the sustainability of the bank's business, so that the bank becomes an environmentally friendly bank and gains social legitimacy from stakeholders. This study aims to determine whether there is an effect of green accounting on CSRDi and financial performance, the effect of financial performance on CSRDi, green accounting on CSRDi with financial performance as an intervening variable, and how the concept of green accounting on CSRDi and financial performance at Islamic Commercial Banks in Islamic perspective. . This study uses a descriptive quantitative approach using multiple linear regression analysis and path analysis. Population and sample in this study are all Islamic Commercial Banks for the period 2015-2018 that meet the criteria. The dependent variable (X) is green accounting with the dummy method, the independent variable (Y) is CSR disclosure with the G.R.I 3.0 version of the CSR disclosure indicator, and the intervening variable (Z) is financial performance calculated using the ROA ratio. The results of this study are green accounting has a positive and significant effect on CSRDi and financial performance, financial performance has a positive and significant effect on CSR In, financial performance is not an intervening variable on green accounting for CSRDi, green accounting for CSRDi on BUS is in accordance with the Islamic perspective both in implementationandassessment. Keywords: Green Accounting, Corporate Social Responsibility Disclosure (CSRDi), Financial Performance, Return On Assets (ROA)